Biomimetic synthesis and anti-inflammatory effects of horsfiequinone A. (16th February 2021) - Wang, Mei; Liu, Yuan-Lie; Li, Dashan; Xiao, Wen-Wen; Chen, Yang; Zhang, Hong-Lin; Zhan, Rui; Shao, Li-Dong
Graphical abstract: Highlights: A biomimetic total synthesis of horsfiequinone A. Aerobic copper-catalyzed oxidation. The anti-inflammatory activity of horsfiequinone A was revisited. Abstract: Inspired by the oxy-tyrosinase type II copper enzyme, a biomimetic synthesis of the natural product horsfiequinone A (1 ) has been achieved using CuOTf/DBED/O2 catalyzed oxidation as a key step. The synthetic route furnished 1 in 33% overall yield (64% brsm) from commercially available para-hydroxybenzaldehyde. Moreover, revisiting the biological activity of 1 resulted in the discovery of its in vitro inhibitory activity towards nitric oxide (NO) production in LPS-induced RAW264.7 cells with an IC50 value of 4.42 ± 0.81 μM. The anti-inflammatory effect of 1 was further supported by an iNOS expression inhibition assay and molecular docking simulation.